Survey of Speed and Agility Physical Conditions in Jombang Basketball Club Athletes - Yudi Dwi Saputra; Nurdian Ahmad; Basuki (Universitas Majalengka, 2023)
In the survey that has been carried out, the team athletes from Jombang Basketball Club seem unable to be consistent in achieving achievements in several basketball tournaments and matches. The aim of the research was to conduct an assessment of the physical condition which included speed and agility in Jombang basketball club athletes. Both of these components are considered to represent the physical condition of the athletes. The population in this study were all Jombang Basketball Club athlete students as many as 33 athletes. The research instrument used in this study was a physical condition test in basketball. The test used to determine physical condition is for speed using the 30 m sprint test while for agility using the Illinois agility run test. The results obtained for the speed of Jombang Basketball Club athletes are still below the average category because of the 33 total, only 6 people whose speed is in the good category with a percentage of 18%. 21 people in the moderate category with a percentage of 64% and 6 people in the less category with a percentage of 18%. While agility is also categorized as still below average because of the 33 total, only 4 people whose agility is in the good category with a percentage of 12%. 18 people in the moderate category with a percentage of 55% and 11 people in the less category with a percentage of 33%. Based on data analysis it can be concluded in general that the level of physical condition of Jombang Basketball Club athletes is still below average as a basketball athlete, therefore both athletes and coaches must continue to work together to implement and carry out training programs so that speed and agility can increase to support performance.